Pancreas outcomes between living and deceased kidney donor in pancreas after kidney transplantation patients. Issue 11 (8th June 2018) - Ventura-Aguiar, Pedro; Ferrer, Joana; Revuelta, Ignacio; Paredes, David; de Sousa-Amorim, Erika; Rovira, Jordi; Esmatjes, Enric; Garcia-Valdecasas, Juan Carlos; Campistol, Josep M; Oppenheimer, Federico; Diekmann, Fritz; Ricart, Maria José
Abstract: Background: Pancreas outcomes in pancreas after kidney transplantation (PAK) patients have been reported as being inferior to those of patients who receive simultaneous pancreas and kidney transplantation (SPK). The influence of the kidney donor (i.e. living versus deceased) has never been previously addressed. Methods: We retrospectively analysed all pancreas transplants performed in a single centre since 2007 and compared the outcomes between those patients who had previously received a living-donor kidney transplant (pancreas transplantation after living-donor kidney transplantation, PAldK; n = 18) or a deceased-donor kidney transplant (pancreas transplantation after deceased-donor kidney transplantation, PAddK; n = 28), using SPK ( n = 139) recipients as a reference. Results: Pancreas survival was similar between all groups, but inferior for PAldK when including only those with a functioning graft at day 90 post-transplantation (P = 0.004). Pancreas acute rejection was significantly increased in PAldK (67%; 1.8 ± 1.4 episodes/graft) when compared with PAddK (25%) and SPK (32%) (P < 0.05) patients. In a multivariate Cox regression model including known risk factors for pancreas rejection, PAldK was the only predictor of acute rejection (hazard ratio 6.82, 95% confidence interval 1.51–30.70, P < 0.05). No association was found between donor–recipient HLA mismatches and graft rejection. Repeated HLA mismatches between kidney and pancreas donors (0 versus 1–6) did not correlate with pancreas graft rejection or survival in either PAK transplantation group (P > 0.05). Conclusion: Pancreas graft outcomes are worse for PAldK when compared with PAddK and SPK patients.